Don't help them to bury the light. The interplay between intersystem crossing and hydrogen transfer in photoexcited curcumin revealed by surface-hopping dynamics. Issue 43 (29th October 2021) - Losantos, Raul; Pasc, Andreea; Monari, Antonio
Abstract : Curcumin is a natural compound extracted from turmeric ( Curcuma longa ), which has shown remarkable anti-inflammatory, antibacterial, and possibly anticancer properties; its photophysical properties are explored via non-adiabatic molecular dynamics. Abstract : Curcumin is a natural compound extracted from turmeric ( Curcuma longa ), which has shown remarkable anti-inflammatory, antibacterial, and possibly anticancer properties. The intense absorption in the visible domain and the possibility of intersystem crossing make curcumin attractive also for photodynamic therapy purposes. In the present contribution, we unravel, thanks to non-adiabatic surface hopping dynamics, the interplay between intersystem crossing and hydrogen transfer in the enol form, i.e . the most stable tautomer of curcumin. Most notably, we show that while hydrogen transfer is ultrafast and happens in the sub-ps regime, intersystem crossing is still present, as shown by the non-negligible population of the triplet state manifold after 2 ps. Hence, while the hydrogen transfer channel can act as a deactivating channel, curcumin, also in the red-shifted absorption enol form, can still be regarded as potentially favorable for photodynamic therapy applications.